Development of a rapid one-step immunochromatographic assay for HCV core antigen detection - Mikawa, Angela Yumico [UNESP]; Tagliavini Santos, Sandra Antonia [UNESP]; Kenfe, Flavia Regina [UNESP]; da Silva, Flavio Henrique; da Costa, Paulo Inacio [UNESP] (Elsevier B.V., 2009)
The hepatitis C virus (HCV) core protein possesses amino acid sequences highly conserved among HCV isolates and has proved useful for various diagnostic tests. To date, no information has been published regarding the development of an immunochromatographic test for HCV core antigen detection. Therefore, the aim of this research was to develop a rapid, easily performed, highly sensitive and specific test for detection of the HCV core antigen, based on the immunochromatographic strip. The genomic region encoding the core protein (amino acids 1-136) of the hepatitis C virus was expressed in Escherichia coli as a recombinant fusion protein with glutathione S-transferase (GST) cloned into the prokaryotic expression vector pET42a and was confirmed by immunological detection with HCV positive serum. Positive reactions were detected weakly at a 1:15 dilution of the serum and more strongly in 1:10, 1:5, 1:2 and 1:1 dilutions, by the immunochromatographic test. In addition, the test was capable of detecting 0.25-12.0 mu g of the recombinant protein. This immunochromatographic technique opens new perspectives for the diagnosis of hepatitis C during the early seroconversion phase and for a rapid core antigen detection. Published by Elsevier B.V.
Keywords: Hepatitis C virus; Core protein; Antigen; Antibody; Immunochromatographic test